Comprehensive Stroke Centers May Be Associated With Improved Survival in Hemorrhagic Stroke. Issue 5 (6th May 2015) - McKinney, James S.; Cheng, Jerry Q.; Rybinnik, Igor; Kostis, John B.; ,
Abstract : Background: Comprehensive stroke centers (CSCs) provide a full spectrum of neurological and neurosurgical services to treat complex stroke patients. CSCs have been shown to improve clinical outcomes and mitigate disparities in ischemic stroke patients. It is believed that CSCs also improve outcomes in hemorrhagic stroke. Methods and Results: We used the Myocardial Infarction Data Acquisition System (MIDAS) database, which includes data on patients discharged with a primary diagnosis of intracerebral hemorrhage (ICH; International Classification of Diseases, Ninth Revision [ICD‐9] 431) and subarachnoid hemorrhage (SAH; ICD‐9 430) from all nonfederal acute care hospitals in New Jersey (NJ) between 1996 and 2012. Out‐of‐hospital deaths were assessed by matching MIDAS records with NJ death registration files. The primary outcome variable was 90‐day all‐cause mortality. The primary independent variable was CSC versus primary stroke center (PSC) and nonstroke center (NSC) admission. Multivariate logistic models were used to measure the effects of available covariates. Overall, 36 981 patients were admitted with a primary diagnosis of ICH or SAH during the study period, of which 40% were admitted to a CSC. Patients admitted to CSCs were more likely to have neurosurgical or endovascular interventions than those admitted to a PSC/NSC (18.9% vs. 4.7%; P <0.0001). CSC admission was associated with lower adjusted 90‐day mortality (35.0% vs. 40.3%; odds ratio, 0.93; 95% confidence interval, 0.89 to 0.97) for hemorrhagic stroke. This was particularly true for those admitted with SAH. Conclusions: Hemorrhagic stroke patients admitted to CSCs are more likely to receive neurosurgical and endovascular treatments and be alive at 90 days than patients admitted to other hospitals.